2010
DOI: 10.4314/pamj.v5i1.56176
|View full text |Cite
|
Sign up to set email alerts
|

The burden experienced by family caregivers of patients with epilepsy attending the government psychiatric hospital, Kaduna, Nigeria

Abstract: BACKGROUND: Caring for patients with chronic medical and psychiatric disorders is associated with significant burden. However little is known about the burden experience by caregivers of patients with epilepsy in Nigeria. The objective of this study, therefore, was to assess the level and correlates of burden among caregivers of patients with epilepsy. METHODS: It was a cross-sectional study carried out among 231 eligible caregivers of patients with epilepsy attending the psychiatric clinic of government psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 14 publications
(2 reference statements)
5
24
3
Order By: Relevance
“…This agrees with the findings from a study conducted in Northern Nigeria in 2010, which revealed that most of the care giving family members of patients with epilepsy were parents (62.7%) or spouses (17.7%) [9]. Spouses had a high degree of burden (33.9%), which is statistically significant across the other levels of relationship to the patients (p-value < 0.001).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This agrees with the findings from a study conducted in Northern Nigeria in 2010, which revealed that most of the care giving family members of patients with epilepsy were parents (62.7%) or spouses (17.7%) [9]. Spouses had a high degree of burden (33.9%), which is statistically significant across the other levels of relationship to the patients (p-value < 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…The total burden score for a participant is the sum of the scores in all the items. This tool has been validated and used in a number of studies involving caregiver burden in Nigeria [4,9,13,14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 However, cultural views and superstition about mental illness persist in many parts of the country and still affect care of the mentally ill, and by extension also affect the caregiver. Very limited research has been conducted locally on this subject 23,24,25 , and this study will hopefully add to efforts in this area. The investigator's main purpose in the study was to determine the psychological factors, distress and the experience of burden of care among caregivers with the aim of contributing towards planning relevant culturally sensitive interventions to improve the wellbeing of caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, studies have identified a bi-directional relationship between caregiving burden and psychological distress among patients with various chronic medical illnesses [13,15,16]. Unfortunately, while caregiver burden has been extensively examined in relation to many chronic illnesses [15][16][17][18][19], there appears to be none among caregivers of children with OAT. Similar scenarios have been reported in the developed world [15] as caregivers have often been referred to as the hidden patients [16].…”
mentioning
confidence: 99%